Understanding Sabah exemplary interfaith relations from a grassroots perspective - Suraya Sintang (ISEAS, 2024)
In contrast to Peninsular Malaysia’s inter-ethnic and inter-religious relations, which are often tense and acrimonious, Sabah manifests a remarkable degree of cohesion, mutual respect and accommodation in relations among its diverse racial and religious communities. Sabahans consider interfaith relations, mostly represented by Muslim-Christian interactions, as a bond between brothers and sisters, different from the superior-inferior and majority-minority dynamics found elsewhere. Building on previous qualitative studies and content analysis, this paper argues that this fraternal friendship found in Sabah’s inter-religious relations can be attributed to familial attitudes and outlooks. These express genuine respect towards other religions and a commitment to nurture peace in society by demonstrating openness to differences, and a willingness to live in close proximity to each other. This paper aims to elucidate some indicators of socio-religious harmony in Sabah and identify factorsthat contribute to the tolerant coexistence of its diverse groups of people. While the government’s initiatives remain important, longstanding practices at the grassroots level, such as interfaith marriages and mixed-faith families are fundamental forces that foster tolerance, understanding, and harmony.